Investigation on the infection of Chinese sacbrood virus and Melissococcus pluton in Chinese honeybee (Apis cerana cerana) of Chun’an County of Zhejiang Province - WANG Deqian; HUANG Minjie; GUO Haikun; FANG Mengge; LI Junzhu; DONG Jie (浙江大学学报. 农业与生命科学版)
In order to understand the annual epidemic situation of Chinese sacbrood disease and European foulbrood disease pathogens [Chinese sacbrood virus (CSBV) and Melissococcus pluton, respectively] in Chinese honeybee (Apis cerana cerana) of Chun’an County of Zhejiang Province, the workers in Chinese honeybee colonies were collected from five breeding sites in Chun’an County from January to December in 2019, and the dynamic changes of the two main disease pathogens in the Chinese honeybee colonies were monitored by polymerase chain reaction (PCR). The results showed that the colony infection rate of CSBV was the highest in March of spring (84%), and it decreased to the lowest in July of summer, then increased from autumn to winter. The infection rate of M. pluton increased from spring to summer, and then increased from autumn to the highest level of 72% in late autumn (October) and early winter (November), and decreased slightly in winter. Furthermore, there was co-infection phenomenon of these two disease pathogens in honeybee colonies in the whole year. The results of real-time quantitative PCR showed that the viral load of CSBV in colonies with M. pluton in autumn was significantly higher than that in the colonies with a single infected CSBV (P＜0.05). In conclusion, the annual epidemic dynamics of two main disease pathogens of Chinese honeybee is clarified in Chun’an County of Zhejiang Province, which can provide theoretical guidances for the prevention and control of Chinese honeybee diseases in this region.